Role of RhoC in cancer cell migration - Yingyue Lou; Yuhan Jiang; Zhen Liang; Bingzhang Liu; Tian Li; Duo Zhang (Cancer Cell International, 2021)
Abstract Migration is one of the five major behaviors of cells. Although RhoC—a classic member of the Rho gene family—was first identified in 1985, functional RhoC data have only been widely reported in recent years. Cell migration involves highly complex signaling mechanisms, in which RhoC plays an essential role. Cell migration regulated by RhoC—of which the most well-known function is its role in cancer metastasis—has been widely reported in breast, gastric, colon, bladder, prostate, lung, pancreatic, liver, and other cancers. Our review describes the role of RhoC in various types of cell migration. The classic two-dimensional cell migration cycle constitutes cell polarization, adhesion regulation, cell contraction and tail retraction, most of which are modulated by RhoC. In the three-dimensional cell migration model, amoeboid migration is the most classic and well-studied model. Here, RhoC modulates the formation of membrane vesicles by regulating myosin II, thereby affecting the rate and persistence of amoeba-like migration. To the best of our knowledge, this review is the first to describe the role of RhoC in all cell migration processes. We believe that understanding the detail of RhoC-regulated migration processes will help us better comprehend the mechanism of cancer metastasis. This will contribute to the study of anti-metastatic treatment approaches, aiding in the identification of new intervention targets for therapeutic or genetic transformational purposes.